A DISCOURSE ANALYSIS OF THE NEWSPAPER ADVICE COLUMN - Mary Ann Malimas (PEOPLE: International Journal of Social Sciences, 2025)
This study investigated the feminist voice revealed in the advice-transaction column Women’s World, Sunday issues of SunStar Daily newspaper. Specifically, as implied by the verbal transaction, it focuses on these feminist aspects: societal roles of women as advice-seekers and as advice-givers. Also, this research illustrated the socio-psychological thematic issues involved in this advice column. The data of this study are the advice columns in the Women’s World published in SunStar Daily every Sunday of the week where twenty-two issues were examined. The results showed that women face particular and complicated obstacles in life and play a variety of roles in society. Their varied experiences have revealed insightful facts, such as the fact that women worry about things like their weight and appearance, matriarchal obligations, relationships, and career goals, among other things. These problems provide as an example of the intricate and varied difficulties that women encounter in daily life. The study found that women who seek guidance have a number of socio-psychological issues that represent the worries and difficulties they face in their daily lives, including psychological issues, relationship infidelity, family troubles, commitment uncertainty, and professional obstacles. The study also emphasizes the significant contribution that women have as advice-givers in newspaper advice columns. Women offer guidance on a range of subjects, such as family problems, romantic relationships, and raising kids. This conclusion emphasizes the importance of women’s support and guidance of others and the necessity for support systems that empower women to have fulfilled lives.